Morphological characterization of the venom secretory epidermal cells in the stinger of marine and freshwater stingrays - Pedroso, Catia M.; Jared, Carlos; Charvet-Almeida, Patricia; Almeida, Mauricio P.; Neto, Domingos Garrone; Lira, Marcela S.; Haddad, Vidal; Barbaro, Katia C. (Elsevier B.V., 2007)
Marine and freshwater stingrays are characterized by the presence of one to three mineralized serrated stingers on the tail, which are covered by epidermal cells secreting venom. When these animals are dorsally touched, the stinger can be introduced into the aggressor by a whip reflex mechanism of the tail, causing severe mechanical injuries and inoculating the venom. Accidents in humans are frequent causing intense local pain, oedema and erythema. Bacterial secondary infection is also common. In addition, injuries involving freshwater stingrays frequently cause a persistent cutaneous necrosis. The exact localization of the venom secretory epidermal cells in the stinger is controversial, but it is known that it is preferentially located in the ventrolateral grooves. A comparative morphological analysis of the stinger epidermal tissue of different marine and freshwater Brazilian stingray species was carried out. The results indicate that in freshwater species there is a larger number of protein secretory cells, of two different types, spread over the whole stinger epidermis, while in marine species the protein secretory cells are located only around or inside the stinger ventrolateral grooves. These differences between the stingers of the two groups can justify the more severe envenomation accidents with the freshwater species when compared with the marine species. (c) 2007 Elsevier Ltd. All rights reserved.
Keywords: stingrays; venoms; Dasyatis; Aetobatus; PotamotrYgon